TEKNIK MEMBACA - MENGINGAT-INGA-T BAHAN PENULISAN KARYA LLMIAH - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
As we are seen, personal progression involves the development  of knowledge, skills and  attitudes  in all areas and  the  development of  whole   person  as  an  individual and  as a  member   of  society. How ever learning  as a tool by itself can  tie limited  ettectiveness. What  is  learning?   Learning  is  defined   as a  reJatively  permanent change   in  behavior  that  occurs.  For most student   an  effective approach  is  to scan _the  study guide,  the chapter   focus and  study outline sections. Read  the text carefully and making  notes. Designing  or enriching activities  intended  to help  the students  to gain more  knowledge and skills.A team  researchers  developed  a program to help  students  how to read  with a purpose.  How to get  them more actively  involved  in the material  they read. How    to    read    effectively   and    productively.    Reading    and remembering   technique,   a    more    recent     variation     of    this technique  is  called   the  PQ4R technique  introduced  by  Thomas and  Robinson ( 1972).